On the Penetration of Projectiles into Semi-Infinite Concrete Targets in a Coupled Deforming and Eroding Regime - Hengwei Xu; Yonggang Lu; Junrun Li; Xing Chen; Xiaowei Feng; Zhengcao Lu (Buildings)
With the advancement of high-velocity kinetic energy weapons, the impact velocity encountered by concrete protective structures has evolved from low to high velocity ranges, rendering traditional rigid projectile penetration theories inadequate for accurately describing the physical mechanisms of deformation and erosion coupling during penetration. This study establishes a theoretical analytical framework for penetration dynamics under high-velocity conditions with coupled deformation and erosion effects: the critical velocity threshold distinguishing between rigid projectile penetration and hydrodynamic penetration modes is precisely defined based on the initial impact velocity V0. By integrating empirical mass erosion formulas with cavity expansion theory, a theoretical model encompassing coupled deformation and erosion effects has been developed, incorporating both projectile cross-sectional area evolution and penetration depth prediction. Comparative analysis with published experimental data (small-scale projectiles vertically impacting concrete targets) demonstrates the model’s predictive accuracy, showing maximum errors of 9.5% in critical velocity prediction, 17.89% in projectile cross-sectional area prediction, and 24.4% in penetration depth prediction.